2007
DOI: 10.1080/13651500600969129
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antidepressants in the treatment of major depressive disorder in Latin America

Abstract: Objective. Painful physical symptoms occur frequently in patients with major depressive disorder (MDD), and although numerous studies report the effect of antidepressants on emotional aspects of depression, few focus on their effect on physical symptoms. This observational study was conducted, in a clinical practice setting, to determine antidepressant treatment decisions and their outcome on the physical and emotional symptoms of MDD. Methods. Patients with a mean score ≥2 for pain-related items on the Somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
3
2
0
2
Order By: Relevance
“…In the same study, patients who achieved remission and partial response in terms of their depressive symptoms also experienced significantly greater improvement than non‐responders in both painful and non‐PPS after 3 months (30). Similar results were observed in a Latin American observational study, where PPS+ patients improved less than PPS− patients on depression and pain outcomes, and were less likely to achieve remission during the 12‐month study period (31). Comparable findings were observed in this study, where PPS+ patients had improved less on depression, pain and quality of life measures after 3 months treatment and, while response rates were statistically similar between PPS groups, fewer PPS+ patients had achieved symptomatic remission during the study.…”
Section: Discussionsupporting
confidence: 79%
“…In the same study, patients who achieved remission and partial response in terms of their depressive symptoms also experienced significantly greater improvement than non‐responders in both painful and non‐PPS after 3 months (30). Similar results were observed in a Latin American observational study, where PPS+ patients improved less than PPS− patients on depression and pain outcomes, and were less likely to achieve remission during the 12‐month study period (31). Comparable findings were observed in this study, where PPS+ patients had improved less on depression, pain and quality of life measures after 3 months treatment and, while response rates were statistically similar between PPS groups, fewer PPS+ patients had achieved symptomatic remission during the study.…”
Section: Discussionsupporting
confidence: 79%
“…Another study conducted with a sample of elderly Chinese patients observed that pain at baseline predicted depressive symptoms at the 12‐month follow‐up assessment (Chou & Chi, ). Similar findings have been reported in other regions, eg, in a Latin American observational study (Dueñas et al, ), which reported that patients with pain improved less than patients with no pain in depression outcomes and had a reduced quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations have been consistently reported across various ethnicities (Muñoz et al 2005;Husain et al 2007). In a Latin American study, PPS1 patients improved less than PPS À patients on depression and pain outcomes over a 12-month period (Dueñas et al 2007). In a randomized clinical trial conducted in the United States, baseline pain severity was a strong predictor of poor antidepressant treatment response and poor quality of life after 3 months of study (Bair et al 2003;Meyer et al 2007).…”
Section: Discussionsupporting
confidence: 76%
“…2007). In a Latin American study, PPS+ patients improved less than PPS− patients on depression and pain outcomes over a 12‐month period (Dueñas et al . 2007).…”
Section: Discussionmentioning
confidence: 99%